The point of no return? Restrictive changes to lenient return policies and consumer reactions to them - Abdulla, Huseyn; Ketzenberg, Michael; Abbey, James D.; Heim, Gregory R. (Journal of Operations Management, 2025)
Abstract Retailers face a challenging trade‐off in maintaining versus restricting long‐established lenient return policies. On the one hand, lenient return policies have become an important part of retailers' value propositions and play a significant role in stimulating consumer purchases. On the other hand, lenient return policies increase the volume of product returns, which hurts profitability. Motivated by observing an increase in restrictive changes to long‐established lenient return policies, we investigate consumer reactions to such changes and their managerial implications. Through a series of experiments with diverse consumer samples, we find that restrictive changes, such as shortening return time windows or introducing restocking fees, decrease consumer trust in retailers and lead to lowered purchase, positive word‐of‐mouth, and loyalty intentions. We also find that providing managerial transparency, in the form of communicating the rationale for restrictive changes, can attenuate the negative consumer reactions to such changes. Moreover, rationales that emphasize the cost of handling returns versus blaming opportunistic and abusive returners are similarly effective. Our findings contribute to the growing academic literature on consumer return policy design and provide actionable insights to retail managers.